Gambaran Sikap Peserta Pada Pelatihan Manajemen Terapan Bagi Pengelola Program Kesehatan (Applied Management Training Course / AMTC) di Balai Besar Pelatihan Kesehatan Ciloto pada Tahun 2019 - Rieka Siti Kadaria (Pusat Pembinaan Jabatan Fungsional Bidang Pengembangan Kompetensi Pegawai ASN, 2019)
As a unit that provides education and training services, Health Training Center (BBPK) is supposed to measure trainees’ attitudes through a survey so that education and training managers can listen to trainees’ voices regarding their wants, needs, and expectations towards the implementation of education and training at BBPK Ciloto. This research is conducted to find out the description of the trainees’ attitudes, and supporters and inhibitors of AMTC Training in 2019 using the ‘sandwich’ method which is somewhat different from the usual trainings because it has long hours of learning that are intermittently alternated between on-class and off-class. This training uses descriptive qualitative quantitative approach to obtain the information through participatory observation and in-depth interviews that generate descriptive data in order to reveal the causes and processes of the events under study. The information is collected from respondents using a questionnaire. Results shows that the training using the ‘sandwich’ pattern reveals the attitude of the trainees being able to prioritize problems, analyze problems deeper, find solutions, share and coordinate well, work more carefully, more thoroughly, more directly and on target, think systematically and be able to be leaders. In this study, it is also noticed that Leaders and Teams formed by the trainees are very supportive of the implementation in the field. While the number of daily work in the office makes it difficult to divide time between office assignments and training assignments when off class. It is expected that in the future BBPK Ciloto will be able to provide and give better services in terms or organizing education and training in accordance with the wants, needs and expectations from all training participants.